Pengaruh Pemberian Obat Antidepresan terhadap Risiko Bunuh Diri: Literatur Review - Febi Febriani Hasanah; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Depression is a mental health disorder that often occurs to anyone regardless of age. Treatment of depression can be done with psychotherapy, administration of antidepressants, or a combination of both. However, the use of antidepressants is believed to increase the risk of suicidal behavior and ideation, especially in adolescent patients. The purpose of this study was to determine the effect of antidepressant therapy on the risk of suicide in adolescents. This research was conducted using the Literature Review method using the Google Scholar database. Articles obtained from the search process were then re-selected based on inclusion and exclusion criteria, so that 5 articles that match the criteria were obtained. The results of the study show that giving antidepressant drugs to patients can increase or decrease the risk of suicide in patients. Patients aged <18 years (children and adolescents) are considered to have a greater risk of suicide compared to adult and geriatric patients. Based on these results, it can be concluded that the use of antidepressant drugs must be done wisely. Patients need to receive supervision and support from the closest people in using antidepressant drugs to avoid the risk of suicide in patients.